Flavone C-glycosides from Dendrobium gratiosissimum. (April 2023) - Song, Zhijun; Liu, Jimei; Li, Changkang; Sun, Xincheng; Chen, Dawei; Chen, Ridao; Xie, Kebo; Han, Yaotian; Dai, Jungui
Abstract: A phytochemical investigation of Dendrobium gratiosissimum Rchb. f. (Orchidaceae) led to the isolation of four new ﬂavone C -glycosides (1 −4 ) together with four known ones (5 −8 ). The chemical structures of the new ﬂavone C -glycosides (1 −4 ) were elucidated by extensive spectroscopic data analysis including 1D- and 2 D NMR, HR-ESI-MS, ESI-MS 2 and careful comparison of the sugar unit spectroscopic data with those of reported in the literature. Biological assay revealed that compounds 6 and 7 showed moderate cytotoxicity against the human tumor cell line HepG2 by suppressing cell viability with an inhibition rate of 76.7 % and 79.6 % at 10.0  μ M, respectively. Graphical Abstract: ga1 Highlights: Eight ﬂavone C -glycosides (1 −8 ), were firstly obtained from Dendrobium gratiosissimum . The structures of the new compounds were elucidated on the basis of extensive spectroscopic data analysis. The results provide supportive experimental evidence for the folkloric use of Dendrobium gratiosissimum as the TCM 'Shi Hu'.